New Perspectives on Depreciation Shocks as a Source of Business Cycle Fluctuations - Francesco Furlanetto; Martin Seneca (Norges Bank, 2011)
In this paper we study the transmission for capital depreciation shocks. The existing literature in the Real Business Cycle tradition has concluded that these shocks are irrelevant for business cycle fluctuations. We show that these shocks are potentially important drivers of aggregate fluctuations in a New Keynesian model. Nominal rigidities and some persistence in the shock process are the key ingredients to generate co-movement across real variables.
hdl:11250/2496962
Keywords: E32; 330; depreciation shocks; investment-specific technology shocks; consumption; nominal rigidities; co-movement